Measurement of multijet azimuthal correlations and determination of the strong coupling in proton-proton collisions at s = 13 Te V - CMS Collaboration (The European physical journal. C, Particles and fields, 2024)
A measurement is presented of a ratio observable that provides a measure of the azimuthal correlations among jets with large transverse momentum p T . This observable is measured in multijet events over the range of p T = 360 - 3170 Ge V based on data collected by the CMS experiment in proton-proton collisions at a centre-of-mass energy of 13 Te V , corresponding to an integrated luminosity of 134 fb - 1 . The results are compared with predictions from Monte Carlo parton-shower event generator simulations, as well as with fixed-order perturbative quantum chromodynamics (pQCD) predictions at next-to-leading-order (NLO) accuracy obtained with different parton distribution functions (PDFs) and corrected for nonperturbative and electroweak effects. Data and theory agree within uncertainties. From the comparison of the measured observable with the pQCD prediction obtained with the NNPDF3.1 NLO PDFs, the strong coupling at the Z boson mass scale is α S ( m Z ) = 0.1177 ± 0.0013 (exp) - 0.0073 + 0.0116 (theo) = 0 . 1177 - 0.0074 + 0.0117 , where the total uncertainty is dominated by the scale dependence of the fixed-order predictions. A test of the running of α S in the Te V region shows no deviation from the expected NLO pQCD behaviour.